Rekonstruksionalisme Pendidikan Formal sebagai Agen Utama dalam Tatanan Sosial - Amar Ma'ruf; Abd. Rachman Assegaf (Maharot : Journal of Islamic Education, 2021)
The position of Islamic religious education is very important and strategic in the implementation of education at every level and type of education. However, in reality, the implementation of Islamic religious education organized by schools/madrasas is still reaping problems and criticism from various parties. And to overcome all the shortcomings and weaknesses of the practice of Islamic religious education in the field, at least a path of change must be taken. For this reason, it is necessary to build and review through what is called the reconstruction of Islamic religious education. These efforts can be carried out through: first, interconnecting Islamic religious education with other lessons; second, doing or creating a religious atmosphere in schools/madrasas. Science is a knowledge that must be owned by a person. Science is taught to a person or student who is researched by universities where the community must also play a role in education, in each study it usually has sub-disciplines and each one is often artificial. the curriculum which is marketing oriented, even to the delinquency of students. All the problems or problems seemed to only be poured out on one party, namely the place of education, while as if not realizing that he had been a student there. There is a sense of dissatisfaction with the performance of national education.